2020
DOI: 10.1016/j.msard.2020.102306
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in 7 multiple sclerosis patients in treatment with ANTI-CD20 therapies

Abstract: Background and aim: In December 2019, the first cases of SARS-CoV-2 infection were detected in Wuhan. Within two months, it had begun to spread around the world in what became an unprecedented pandemic. Patients with Multiple Sclerosis (MS) in a state of immunosuppression may be considered at risk for complications in the COVID-19 pandemic, although there is increasing evidence postulating a possible protective role of selective immunosuppression. One group of such immunosuppressants used in MS comprises the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 10 publications
6
66
0
1
Order By: Relevance
“…A quarter of these participants made the decision without the input of their neurologist. Although it is plausible that high efficacy therapies confer risk of worse outcomes in COVID-19, (Wijnands et al, 2018 Oct;Grebenciucova and Pruitt, 2017;Luna et al, 2020) not all data demonstrate as negative of a prognosis as first may have been feared (Meca-Lallana et al, 2020;Hsu et al, 2020;Mathies et al, 2020;Zhu et al, 2020;Novi et al, 2020). Some authors have posited that immunosuppression is protective due to the inflammatory nature of the SARS-CoV2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A quarter of these participants made the decision without the input of their neurologist. Although it is plausible that high efficacy therapies confer risk of worse outcomes in COVID-19, (Wijnands et al, 2018 Oct;Grebenciucova and Pruitt, 2017;Luna et al, 2020) not all data demonstrate as negative of a prognosis as first may have been feared (Meca-Lallana et al, 2020;Hsu et al, 2020;Mathies et al, 2020;Zhu et al, 2020;Novi et al, 2020). Some authors have posited that immunosuppression is protective due to the inflammatory nature of the SARS-CoV2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some expert groups have recommended delaying or modifying administration of DMTs for patients on alemtuzumab, cladribine, ocrelizumab, or rituximab during COVID-19. (National Multiple Sclerosis Society, 2020;Multiple Sclerosis Society, 2020;MS International Federation, 2020;MS Australia, 2020;Brownlee et al, 2020) More recent data suggest that not all cases of COVID-19 are severe, even while taking some of the high-efficacy therapies for MS (Meca-Lallana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A beneficial effect on the inflammatory response to SARS-CoV2 remains to be confirmed [11], but other immunosuppressive treatments are studied for this purpose [12]. As we observed in 2 patients, anti-CD20 treatment may prevent the development of antibodies targeting SARS-CoV2 [8].…”
mentioning
confidence: 88%
“…It may be related to the young age and low rate of comorbidity in the infected patients. Some authors reported a favorable outcome of COVID-19 in anti-CD20-treated patients [8,9], possibly due to its minor impact on T-cell counts [10]. A beneficial effect on the inflammatory response to SARS-CoV2 remains to be confirmed [11], but other immunosuppressive treatments are studied for this purpose [12].…”
mentioning
confidence: 99%
“…1), suggesting that most MS treatments that largely exhibit limited persistent effects on the innate immune and CD8 T cell responses would have limited influence on COVID‐19. SARS‐CoV‐2 is eliminated by the majority of people with MS and other autoimmunities on immunotherapies, without significant consequences [34–56] (Table 1). Anti‐viral antibodies, notably those targeting the receptor binding domain of the viral spike protein, clearly neutralize the virus [57,58] and can contribute to the elimination of the primary SARS‐CoV‐2 infection in humans [58,59].…”
Section: Introductionmentioning
confidence: 99%